Analisis Kompetensi Guru SMP Negeri di Kabupaten Polman Sulawesi Barat - Husain Syam; Bakhrani A Rauf (Seminar Nasional LP2M UNM, 2022)
Abstract. The purpose of the research is to find out: pedagogic competence, professional competence, personal competence, and social competence of public junior high school teachers in Polman Regency, West Sulawesi. This research is classified as a survey. The research location is Polman Regency, West Sulawesi Province. The determination of the sample schools was carried out by purposive random sampling method. Respondents of the research were certified junior high school teachers. The variables to be considered were: (1) pedagogic competence, (2) professional competence, (3) personal competence, (4) social competence of public junior high school teachers in Polman Regency, West Sulawesi. The analysis used is descriptive analysis. The results showed that: (1) the pedagogical competence of junior high school teachers in Polman Regency, West Sulawesi in the seven aspects studied was classified as high, (2) the professional competence of junior high school teachers in Polman Regency, West Sulawesi in five aspects was classified as high, (3) the personal competence of junior high school teachers in Polman Regency, West Sulawesi in the seven aspects studied are classified as very high, (4) the social competence of junior high school teachers in Polman Regency, West Sulawesi in the four aspects studied is classified as high. Keywords: Junior High School Teachers, Competence, Pedagogical, Professional, and Social.